Inequality at work and employees' perceptions of organisational fairness. Issue 6 (29th September 2021) - Gallie, Duncan; Felstead, Alan; Green, Francis; Henseke, Golo
Abstract: The need to promote fairness at work, as a way of both enhancing employee well‐being and raising productivity, has become increasingly central to political discourse. There has been little research, however, on perceptions of fairness across the diverse spectrum of employees in the workforce—the extent to which they regard their organisations as fair and the work experiences that most strongly inform their judgements about fairness. The paper draws on a representative national sample of British employees to examine the distribution and potential determinants of their views about the overall fairness of their organisations and how these differ by occupational class and sex. As well as pointing to the central importance of employee voice and the quality of supervisory treatment, it shows that the level of work intensity and job security are strongly associated with evaluations of fairness. In contrast, the effects of pay policies are relatively modest.